Experimental imaging and atomistic modeling of electron and hole quasiparticle wave functions inInAs∕GaAsquantum dots - Bester, G.; Reuter, Dirk; He, Lixin; Zunger, A.; Kailuweit, P.; Wieck, A. D.; Zeitler, U.; Maan, J. C.; Wibbelhoff, O.; Lorke, A. (Physical Review B)

Focused ion beam implantation induced site-selective growth of InAs quantum dots - Mehta, M.; Reuter, Dirk; Melnikov, A.; Wieck, A. D.; Remhof, A. (Applied Physics Letters)

Nuclei-Induced Frequency Focusing of Electron Spin Coherence - Greilich, A.; Shabaev, A.; Yakovlev, D. R.; Efros, Al. L.; Yugova, I. A.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Science)

Measurement of the specific heat of a fractional quantum Hall system - Schulze-Wischeler, F.; Zeitler, U.; v. Zobeltitz, C.; Hohls, F.; Reuter, Dirk; Wieck, A. D.; Frahm, H.; Haug, R. J. (Physical Review B)

Systematic study of carrier correlations in the electron-hole recombination dynamics of quantum dots - Berstermann, T.; Auer, T.; Kurtze, H.; Schwab, M.; Yakovlev, D. R.; Bayer, M.; Wiersig, J.; Gies, C.; Jahnke, F.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

The Influence of Device Geometry on Many-Body Effects in Quantum Point Contacts: Signatures of the 0.7 Anomaly, Exchange and Kondo - Koop, E. J.; Lerescu, A. I.; Liu, J.; van Wees, B. J.; Reuter, Dirk; Wieck, A. D.; van der Wal, C. H. (Journal of Superconductivity and Novel Magnetism)

CYCLOTRON RESONANCE IN COUPLED BILAYERS IN HIGH MAGNETIC FIELDS - GÜRTLER, A.; ZEITLER, U.; MAAN, J. C.; Reuter, Dirk; WIECK, A. D. (International Journal of Modern Physics B)

Aharonov-Bohm Oscillations in the Presence of Strong Spin-Orbit Interactions - Grbić, Boris; Leturcq, Renaud; Ihn, Thomas; Ensslin, Klaus; Reuter, Dirk; Wieck, Andreas D. (Physical Review Letters)

Spin Coherence of Holes inGaAs/(Al,Ga)AsQuantum Wells - Syperek, M.; Yakovlev, D. R.; Greilich, A.; Misiewicz, J.; Bayer, M.; Reuter, Dirk; Wieck, A. D. (Physical Review Letters)

Evidence for the Luttigger liquid density of states in transport across the incompressible stripe at fractional filling factors - Deviatov, E. V; Kapustin, A. A; Dolgopolov, V. T; Lorke, A; Reuter, Dirk; Wieck, A. D (Europhysics Letters (EPL))

Hole levels in InAs self-assembled quantum dots - Blokland, J. H.; Wijnen, F. J. P.; Christianen, P. C. M.; Zeitler, U.; Maan, J. C.; Kailuweit, P.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Tuneable photonic crystals obtained by liquid crystal infiltration - Kitzerow, Heinz-Siegfried; Lorenz, A.; Matthias, H. (physica status solidi (a))
Keywords: Materials Chemistry; Electrical and Electronic Engineering; Surfaces; Coatings and Films; Surfaces and Interfaces; Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Liquid crystal director fields in micropores of photonic crystals - Matthias, Heinrich; Schweizer, Stefan L; Wehrspohn, Ralf B; Kitzerow, Heinz-Siegfried (Journal of Optics A: Pure and Applied Optics)
Keywords: Atomic and Molecular Physics; and Optics

Time-Resolved Investigation of Coherently Controlled Electric Currents at a Metal Surface - Gudde, J.; Rohleder, M.; Meier, Torsten; Koch, S. W.; Hofer, U. (Science)
Studies of current dynamics in solids have been hindered by insufficiently brief trigger signals and electronic detection speeds. By combining a coherent control scheme with photoelectron spectroscopy, we generated and detected lateral electron currents at a metal surface on a femtosecond time scale with a contact-free experimental setup. We used coherent optical excitation at the light frequencies ωa and ωa/2 to induce the current, whose direction was controlled by the relative phase between the phase-locked laser excitation pulses. Time- and angle-resolved photoelectron spectroscopy afforded a direct image of the momentum distribution of the excited electrons as a function of time. For the first (n = 1) image-potential state of Cu(100), we found a decay time of 10 femtoseconds, attributable to electron scattering with steps and surface defects.

Polarization-dependent optical 2D Fourier transform spectroscopy of semiconductors - Zhang, T.; Kuznetsova, I.; Meier, Torsten; Li, X.; Mirin, R. P.; Thomas, P.; Cundiff, S. T. (Proceedings of the National Academy of Sciences (PNAS))
Optical 2D Fourier transform spectroscopy (2DFTS) provides insight into the many-body interactions in direct gap semiconductors by separating the contributions to the coherent nonlinear optical response. We demonstrate these features of optical 2DFTS by studying the heavy-hole and light-hole excitonic resonances in a gallium arsenide quantum well at low temperature. Varying the polarization of the incident beams exploits selection rules to achieve further separation. Calculations using a full many-body theory agree well with experimental results and unambiguously demonstrate the dominance of many-body physics.

Optical switching in metallic photonic crystal slabs with photoaddressable polymers - Nau, D.; Bertram, R.P.; Buse, K.; Zentgraf, Thomas; Kuhl, J.; Tikhodeev, S.G.; Gippius, N.A.; Giessen, H. (Applied Physics B)

Metallodielectric photonic crystal superlattices: Influence of periodic defects on transmission properties - Zentgraf, Thomas; Christ, A.; Kuhl, J.; Gippius, N. A.; Tikhodeev, S. G.; Nau, D.; Giessen, H. (Physical Review B)

Resonances of split-ring resonator metamaterials in the near infrared - Rockstuhl, C.; Zentgraf, Thomas; Guo, H.; Liu, N.; Etrich, C.; Loa, I.; Syassen, K.; Kuhl, J.; Lederer, F.; Giessen, H. (Applied Physics B)

Disorder issues in metallic photonic crystals - Nau, D.; Schönhardt, A.; Bauer, C.; Christ, A.; Zentgraf, Thomas; Kuhl, J.; Giessen, H. (physica status solidi (b))

Interaction between localized and delocalized surface plasmon polariton modes in a metallic photonic crystal - Christ, A.; Zentgraf, Thomas; Tikhodeev, S. G.; Gippius, N. A.; Martin, O. J. F.; Kuhl, J.; Giessen, H. (physica status solidi (b))

Controlling the interaction between localized and delocalized surface plasmon modes: Experiment and numerical calculations - Christ, A.; Zentgraf, Thomas; Tikhodeev, S. G.; Gippius, N. A.; Kuhl, J.; Giessen, H. (Physical Review B)

Mapping of the hole wave functions of self-assembled InAs-quantum dots by magneto-capacitance–voltage spectroscopy - Kailuweit, P.; Reuter, Dirk; Wieck, A.D.; Wibbelhoff, O.; Lorke, A.; Zeitler, U.; Maan, J.C. (Physica E: Low-dimensional Systems and Nanostructures)

Enhancement of spin information with vertical cavity surface emitting lasers - Gerhardt, N.; Hövel, S.; Hofmann, M.; Yang, J.; Reuter, Dirk; Wieck, A. (Electronics Letters)

Ballistic rectification in an asymmetric mesoscopic cross junction - Knop, M.; Wieser, U.; Kunze, U.; Reuter, Dirk; Wieck, A. D. (Applied Physics Letters)

Role of quantum capacitance in coupled low-dimensional electron systems - Ruß, M.; Meier, C.; Lorke, A.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Experimental evidence of the ideal de Haas–van Alphen effect in a two-dimensional system - Wilde, M. A.; Schwarz, M. P.; Heyn, Ch.; Heitmann, D.; Grundler, D.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Spin injection light-emitting diode with vertically magnetized ferromagnetic metal contacts - Gerhardt, N. C.; Hövel, S.; Brenner, C.; Hofmann, M. R.; Lo, F.-Y.; Reuter, Dirk; Wieck, A. D.; Schuster, E.; Keune, W.; Halm, S.; Bacher, G.; Westerholt, K. (Journal of Applied Physics)

Influence of a lateral electric field on the optical properties of InAs quantum dots - Reuter, Dirk; Stavarache, V.; Wieck, A.D.; Schwab, M.; Oulton, R.; Bayer, M. (Physica E: Low-dimensional Systems and Nanostructures)

Optical beam-induced current in planar two-dimensional n–p–n devices - Werner, C.; Reuter, Dirk; Wieck, A.D. (Physica E: Low-dimensional Systems and Nanostructures)

Fabrication of genuine single-quantum-dot light-emitting diodes - Schmidt, R.; Scholz, U.; Vitzethum, M.; Fix, R.; Metzner, C.; Kailuweit, P.; Reuter, Dirk; Wieck, A.; Hübner, M. C.; Stufler, S.; Zrenner, A.; Malzer, S.; et al. (Applied Physics Letters)

Optical Control of Spin Coherence in Singly Charged(In,Ga)As/GaAsQuantum Dots - Greilich, A.; Oulton, R.; Zhukov, E. A.; Yugova, I. A.; Yakovlev, D. R.; Bayer, M.; Shabaev, A.; Efros, Al. L.; Merkulov, I. A.; Stavarache, V.; Reuter, Dirk; Wieck, A. (Physical Review Letters)

Tailored quantum dots for entangled photon pair creation - Greilich, A.; Schwab, M.; Berstermann, T.; Auer, T.; Oulton, R.; Yakovlev, D. R.; Bayer, M.; Stavarache, V.; Reuter, Dirk; Wieck, A. (Physical Review B)

Fabrication of submicrometer patterned two-dimensional electron gases by overgrowth of focused ion beam doped Al[sub x]Ga[sub 1−x]As - Reuter, Dirk; Riedesel, C.; Wieck, A. D. (Journal of Vacuum Science & Technology B: Microelectronics and Nanometer Structures)

Correlated electron states at level crossings of bilayer two-dimensional electron systems in tilted magnetic fields - van Tilburg, J.W.W.; Zeitler, U.; Maan, J.C.; Reuter, Dirk; Wieck, A.D.; Biasiol, G.; Sorba, L. (Physica E: Low-dimensional Systems and Nanostructures)

Interaction effects observed in the magnetization of a bilayer two-dimensional electron system - Bominaar-Silkens, I.M.A.; Zeitler, U.; Christianen, P.C.M.; Reuter, Dirk; Wieck, A.D.; Maan, J.C. (Physica E: Low-dimensional Systems and Nanostructures)

Dynamics of nuclear spins appearing in transport measurements of an inter-edge spin diode in tilted magnetic fields - Sukhodub, G.; Hohls, F.; Haug, R.J.; Maude, D.K.; Reuter, Dirk; Wieck, A.D. (Physica E: Low-dimensional Systems and Nanostructures)

Transport spectroscopy of a quantum point contact created by an atomic force microscope - Fricke, C.; Regul, J.; Hohls, F.; Reuter, Dirk; Wieck, A.D.; Haug, R.J. (Physica E: Low-dimensional Systems and Nanostructures)

In-plane tunnelling between one- and two-dimensional electron systems - Deborde, Jean-Laurent; Fischer, Saskia F.; Kunze, Ulrich; Reuter, Dirk; Wieck, Andreas D. (Physica E: Low-dimensional Systems and Nanostructures)

Sticking behavior of the dopants Si, C, and Be upon re-evaporation of individually doped GaAs(100) - Yang, J.L.; Reuter, Dirk; Wieck, A.D. (Journal of Crystal Growth)

Control of quantum dot excitons by lateral electric fields - Stavarache, V.; Reuter, Dirk; Wieck, A. D.; Schwab, M.; Yakovlev, D. R.; Oulton, R.; Bayer, M. (Applied Physics Letters)

1.5 µm luminescence from InAs/GaxIn1–xNyAs1–y quantum dots grown on GaAs substrate - Richter, M.; Hugues, M.; Damilano, B.; Massies, J.; Duboz, J.-Y.; Reuter, Dirk; Wieck, A. D. (physica status solidi (c))

Hole and electron wave functions in self-assembled InAs quantum dots: a comparison - Reuter, Dirk; Kailuweit, P.; Roescu, R.; Wieck, A. D.; Wibbelhoff, O. S.; Lorke, A.; Zeitler, U.; Maan, J. C. (physica status solidi (b))

Sub-second electron spin lifetimes in quantum dots at zero applied magnetic field due to alignment of QD nuclei - Oulton, R.; Verbin, S. Yu.; Auer, T.; Cherbunin, R. V.; Greilich, A.; Yakovlev, D. R.; Bayer, M.; Reuter, Dirk; Wieck, A. (physica status solidi (b))

Scaling of the Low-Temperature Dephasing Rate in Kondo Systems - Mallet, F.; Ericsson, J.; Mailly, D.; Ünlübayir, S.; Reuter, Dirk; Melnikov, A.; Wieck, A. D.; Micklitz, T.; Rosch, A.; Costi, T. A.; Saminadayar, L.; Bäuerle, C. (Physical Review Letters)

Coherent spin oscillations in bulk GaAs at room temperature - Hohage, P. E.; Bacher, G.; Reuter, Dirk; Wieck, A. D. (Applied Physics Letters)

Magnetization of bilayer two-dimensional electron systems - Bominaar-Silkens, I M A; Schaapman, M R; Zeitler, U; Christianen, P C M; Maan, J C; Reuter, Dirk; Wieck, A D; Schuh, D; Bichler, M (New Journal of Physics)

Electron spin coherence in singly charged (In,Ga)As/GaAs quantum dots - Greilich, A.; Oulton, R.; Zhukov, E. A.; Yugova, I. A.; Yakovlev, D. R.; Bayer, M.; Shabaev, A.; Efros, Al. L.; Merkulov, I. A.; Stavarache, V.; Reuter, Dirk; Wieck, A. (physica status solidi (c))

Optical Experiments on Second-Harmonic Generation with Metamaterials Composed of Split-Ring Resonators - Klein, Matthias W.; Enkrich, Christian; Wegener, Martin; Förstner, Jens; Moloney, Jerome V.; Hoyer, Walter; Stroucken, Tineke; Meier, Torsten; Koch, Stephan W.; Linden, Stefan (Photonic Metamaterials: From Random to Periodic)
We study optical second-harmonic generation from planar arrays of magnetic split-ring resonators at 1.5 microns resonance wavelength. We obtain by far the largest signals when exciting the magnetic-dipole resonance.
Keywords: tet_topic_meta

Microscopic analysis of extreme nonlinear optics in semiconductor nanostructures - Golde, Daniel; Meier, Torsten; Koch, Stephan W. (Journal of the Optical Society of America B)
A microscopic analysis is presented for the extreme nonlinear optical response of semiconductor quantum wells and wires after intense excitation with femtosecond laser pulses. In this regime, the light–matter interaction is the dominant eneregy scale, leading to a number of interesting effects such as carrier-wave Rabi flopping, Mollow splitting, and the creation of higher harmonics. The results presented here were obtained by evaluating the semiconductor Bloch equations without the rotating wave approximation. The electronic dispersion of semiconductor nanostructures is shown to have a characteristic influence on the extreme nonlinear optical response, whereas the relative importance of the carrier Coulomb interaction decreases with increasing excitation intensities.

Characterization of Disorder in Semiconductors via Single-Photon Interferometry - Bozsoki, P.; Thomas, P.; Kira, M.; Hoyer, W.; Meier, Torsten; Koch, S. W.; Maschke, K.; Varga, I.; Stolz, H. (Physical Review Letters)
The method of angular photonic correlations of spontaneous emission is introduced as an experimental, purely optical scheme to characterize disorder in semiconductor nanostructures. The theoretical expression for the angular correlations is derived and numerically evaluated for a model system. The results demonstrate how the proposed experimental method yields direct information about the spatial distribution of the relevant states and thus on the disorder present in the system.

Microscopic modeling of the optical properties of semiconductor nanostructures - Thränhardt, A.; Meier, Torsten; Reichelt, Matthias; Schlichenmaier, C.; Pasenow, B.; Kuznetsova, I.; Becker, S.; Stroucken, T.; Hader, J.; Zakharian, A.R.; Moloney, J.V.; Chow, W.W.; et al. (Journal of Non-Crystalline Solids)
A brief overview of a consistent microscopic approach to model the optical and electronic properties of semiconductor nanostructures is presented. Coupled semiconductor Bloch and Maxwell equations are used to investigate the performance of semiconductor microcavity structures, photonic band gap systems, and lasers. The predictive potential of the microscopic theory is demonstrated for several examples of practical importance. Optical gain and output characteristics are computed for modern vertical external cavity surface emitting laser structures. It is shown how design flexibilities can be used to optimize the device performance. Nanostructures are proposed where semiconductor quantum wells are embedded in one-dimensional photonic crystals. For field modes spectrally below the photonic band edge it is shown that the optical gain and absorption can be enhanced by more than one order of magnitude over the value of the homogeneous medium. The increased gain can be used for laser action by placing quantum wells and a suitably designed photonic crystal structure inside a microcavity.

Temporal decay of coherently optically injected charge and spin currents due to carrier–LO-phonon and carrier-carrier scattering - Duc, H. T.; Vu, Q. T.; Meier, Torsten; Haug, H.; Koch, S. W. (Physical Review B)
The coherent ultrafast optical injection and the temporal evolution of charge and spin currents in semiconductors is analyzed using a microscopic many-body theory. The approach is based on the semiconductor Bloch equations and includes light-field-induced intraband and interband excitations, excitonic effects, and carrier–LO-phonon and carrier-carrier scattering processes. The relaxation effects are treated both in the second Born-Markov approximation and on the level of quantum kinetic theory including memory effects. The dynamics of the charge and spin currents is evaluated numerically for a one-dimensional model system. The dependence of the currents and their decay on the temperature, the excitation intensities, and the frequencies of the incident light fields is discussed. Whereas the overall decay dynamics is described well within the Markov approximation, the quantum kinetic theory predicts additional oscillatory signatures in the current transients.

Mode Locking of Electron Spin Coherences in Singly Charged Quantum Dots - Greilich, A.; Yakovlev, D. R.; Shabaev, A.; Efros, Al. L.; Yugova, I. A.; Oulton, R.; Stavarache, V.; Reuter, Dirk; Wieck, A.; Bayer, M. (Science)
The fast dephasing of electron spins in an ensemble of quantum dots is detrimental for applications in quantum information processing. We show here that dephasing can be overcome by using a periodic train of light pulses to synchronize the phases of the precessing spins, and we demonstrate this effect in an ensemble of singly charged (In,Ga)As/GaAs quantum dots. This mode locking leads to constructive interference of contributions to Faraday rotation and presents potential applications based on robust quantum coherence within an ensemble of dots.
Keywords: Multidisciplinary

Waveguide-plasmon polaritons in photonic crystal slabs with metal nanowires - Tikhodeev, S. G.; Gippius, N. A.; Christ, A.; Zentgraf, Thomas; Kuhl, J.; Giessen, H. (physica status solidi (c))

Coulomb-Interaction-Induced Incomplete Shell Filling in the Hole System of InAs Quantum Dots - Reuter, Dirk; Kailuweit, P.; Wieck, A. D.; Zeitler, U.; Wibbelhoff, O.; Meier, Cedrik; Lorke, A.; Maan, J. C. (Physical Review Letters)

Spin controlled optically pumped vertical cavity surface emitting laser - Hövel, S.; Gerhardt, N.; Hofmann, M.; Yang, J.; Reuter, Dirk; Wieck, A. (Electronics Letters)

Depletion characteristics of two-dimensional lateral p‐n-junctions - Reuter, Dirk; Werner, C.; Wieck, A. D.; Petrosyan, S. (Applied Physics Letters)

Exciton dephasing via phonon interactions in InAs quantum dots: Dependence on quantum confinement - Borri, P.; Langbein, W.; Woggon, U.; Stavarache, V.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Optical orientation of electron spins in GaAs quantum wells - Pfalz, S.; Winkler, R.; Nowitzki, T.; Reuter, Dirk; Wieck, A. D.; Hägele, D.; Oestreich, M. (Physical Review B)

Wave-form sampling using a driven electron ratchet in a two-dimensional electron system - Müller, T.; Würtz, A.; Lorke, A.; Reuter, Dirk; Wieck, A. D. (Applied Physics Letters)

Electron spin injection into GaAs from ferromagnetic contacts in remanence - Gerhardt, N. C.; Hövel, S.; Brenner, C.; Hofmann, M. R.; Lo, F.-Y.; Reuter, Dirk; Wieck, A. D.; Schuster, E.; Keune, W.; Westerholt, K. (Applied Physics Letters)

Electrical Readout of the Local Nuclear Polarization in the Quantum Hall Effect: A Hyperfine Battery - Würtz, A.; Müller, T.; Lorke, A.; Reuter, Dirk; Wieck, A. D. (Physical Review Letters)

Single quantum dot nano-LEDs - spectroscopy of an electrically controlled few-particle system - Schmidt, R.; Scholz, U.; Vitzethum, M.; Fix, R.; Malzer, S.; Metzner, C.; Kailuweit, P.; Reuter, Dirk; Wieck, A.; Hübner, M. C.; Stufler, S.; Zrenner, A.; et al. (physica status solidi (c))

Screening effects in InAs quantum-dot structures observed by photoluminescence and capacitance-voltage spectra - Lüttjohann, Stephan; Meier, Cedrik; Lorke, Axel; Reuter, Dirk; Wieck, Andreas D. (Applied Physics Letters)

Single-hole transistor in p-type GaAs∕AlGaAs heterostructures - Grbić, Boris; Leturcq, Renaud; Ensslin, Klaus; Reuter, Dirk; Wieck, Andreas D. (Applied Physics Letters)

Preparation of electron waveguide devices on GaAs/AlGaAs using negative-tone resist calixarene - Knop, M; Richter, M; Maßmann, R; Wieser, U; Kunze, U; Reuter, Dirk; Riedesel, C; Wieck, A D (Semiconductor Science and Technology)

Thermopower of a Kondo Spin-Correlated Quantum Dot - Scheibner, R.; Buhmann, H.; Reuter, Dirk; Kiselev, M. N.; Molenkamp, L. W. (Physical Review Letters)

PHONON EXCITATIONS OF COMPOSITE FERMION LANDAU LEVELS - SCHULZE-WISCHELER, F.; HOHLS, F.; ZEITLER, U.; Reuter, Dirk; WIECK, A. D.; HAUG, R. J. (International Journal of Modern Physics B)

PHONON EXCITATIONS OF COMPOSITE FERMION LANDAU LEVELS - SCHULZE-WISCHELER, F.; HOHLS, F.; ZEITLER, U.; Reuter, Dirk; WIECK, A. D.; HAUG, R. J. (International Journal of Modern Physics B)

Spatially inhomogeneous optical gain in semiconductor photonic-crystal structures - Reichelt, Matthias; Pasenow, B.; Meier, Torsten; Stroucken, T.; Koch, S. W. (Physical Review B)
The optical and electronic properties of semiconductor heterostructures in the vicinity of photonic crystals are discussed. The theoretical approach provides a self-consistent solution of the dynamics of the electromagnetic field and the material excitations. Due to the influence of the structured dielectric environment on the Coulomb interaction, the exciton resonances and the quasiequilibrium carrier densities in the spatially homogeneous semiconductor become space dependent. It is demonstrated that these inhomogeneities lead to distinct modifications of the optical absorption and gain spectra. As an application, numerically calculated density-dependent optical spectra are analyzed for an array of semiconductor quantum wires which are close to a two-dimensional photonic crystal. The spatial inhomogeneities result in novel excitonic absorption features and modification of the optical gain in these structures.

Femtosecond time-resolved five-wave mixing at silicon surfaces - Meier, Torsten; Reichelt, Matthias; Koch, S W; Höfer, U (Journal of Physics: Condensed Matter)
The ultrafast dynamics of photoexcitations at silicon surfaces is investigated using a surface-sensitive purely optical technique. In the experiments, the diffracted second harmonic generated by sequences of ultrashort laser pulses is detected as a function of the time delay between the pulses. It is demonstrated that this five-wave-mixing technique can be used to measure the temporal evolution of the optical polarization and the photoexcited populations at the surface. The experimental results can be reproduced by numerical solutions of optical Bloch equations. The theoretical analysis allows one to investigate which dephasing times and relaxation processes are compatible with experiment. Furthermore, it is outlined how one can describe optical nonlinearities at surfaces using a microscopic theory within the framework of semiconductor Bloch equations.

Optical properties of planar metallic photonic crystal structures: Experiment and theory - Christ, A.; Zentgraf, Thomas; Kuhl, J.; Tikhodeev, S. G.; Gippius, N. A.; Giessen, H. (Physical Review B)

Tailoring the Ultrafast Dephasing of Quasiparticles in Metallic Photonic Crystals - Zentgraf, Thomas; Christ, A.; Kuhl, J.; Giessen, H. (Physical Review Letters)

Coherent dynamics in InGaAs quantum dots and quantum dot molecules - Langbein, W.; Borri, P.; Woggon, U.; Schwab, M.; Bayer, M.; Fafard, S.; Wasilewski, Z.; Hawrylak, P.; Stavarache, V.; Reuter, Dirk; Wieck, A.D. (Physica E: Low-dimensional Systems and Nanostructures)

Magnetic field dependence of hole levels in InAs quantum dots - Reuter, Dirk; Kailuweit, P.; Wieck, A.D.; Zeitler, U.; Maan, J.C. (Physica E: Low-dimensional Systems and Nanostructures)

Preparation and characterization of epitaxial Fe(001) thin films on GaAs(001)-based LED for spin injection - Schuster, E.; Keune, W.; Lo, F.-Y.; Reuter, Dirk; Wieck, A.; Westerholt, K. (Superlattices and Microstructures)

Electroluminescence of single-dot nano-LEDs—optical spectroscopy of an electrically tunable few-electron/hole system - Schmidt, R.; Vitzethum, M.; Fix, R.; Scholz, U.; Malzer, S.; Metzner, C.; Kailuweit, P.; Reuter, Dirk; Wieck, A.; Hübner, M.C.; Stufler, S.; Zrenner, A.; et al. (Physica E: Low-dimensional Systems and Nanostructures)

Dual-gate GaAs/AlGaAs quantum point contact with tuneable subband energy separation - Kähler, D; Knop, M; Kunze, U; Reuter, Dirk; Wieck, A D (Semiconductor Science and Technology)

Ultrasmall nanoscale devices fabricated from compensating-layer GaAs/AlGaAs heterostructures - Kähler, Dirk; Kunze, Ulrich; Reuter, Dirk; D. Wieck, Andreas (Physica E: Low-dimensional Systems and Nanostructures)

The linearly graded two-dimensional p–n junction - Petrosyan, S.; Yesayan, A.; Reuter, Dirk; Wieck, A. D. (Applied Physics Letters)

Laterally patterned high mobility two-dimensional electron gases obtained by overgrowth of focused ion beam implanted Al1−xGaxAs - Riedesel, C; Reuter, Dirk; Wieck, A.D (Physica E: Low-dimensional Systems and Nanostructures)

Frequency-dependent C(V) spectroscopy of the hole system in InAs quantum dots - Reuter, Dirk; Schafmeister, P.; Kailuweit, P.; Wieck, A.D. (Physica E: Low-dimensional Systems and Nanostructures)

Fabrication of two-dimensional n- and p-type in-plane gate transistors from the same p-doped GaAs/In0.1Ga0.9As/Al0.33Ga0.67As heterostructure - Reuter, Dirk; Seekamp, A; Wieck, A.D (Physica E: Low-dimensional Systems and Nanostructures)

High frequency conductance of a quantum point contact - Regul, J.; Hohls, F.; Reuter, Dirk; Wieck, A.D.; Haug, R.J. (Physica E: Low-dimensional Systems and Nanostructures)

Fabrication of two-dimensional p–n junctions formed by compensation doping of p-modulation doped GaAs/InyGa1−yAs/AlxGa1−x As heterostructures - Reuter, Dirk; Werner, C.; Riedesel, C.; Wieck, A.D.; Schuster, D.; Hansen, W. (Physica E: Low-dimensional Systems and Nanostructures)

Self-assembled quantum dots as probes for Landau-level spectroscopy - Russ, M; Lorke, A; Reuter, Dirk; Schafmeister, P (Physica E: Low-dimensional Systems and Nanostructures)

Separately contacted edge states in the fractional quantum Hall regime - Würtz, A.; Deviatov, E.V.; Lorke, A.; Dolgopolov, V.T.; Reuter, Dirk; Wieck, A.D. (Physica E: Low-dimensional Systems and Nanostructures)

Control of fine-structure splitting and biexciton binding inInxGa1−xAsquantum dots by annealing - Langbein, W.; Borri, P.; Woggon, U.; Stavarache, V.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Magnetization of multi-component two-dimensional quantum-Hall systems - Schaapman, M.R.; Zeitler, U.; Christianen, P.C.M.; Maan, J.C.; Reuter, Dirk; Wieck, A.D. (Physica E: Low-dimensional Systems and Nanostructures)

Capacitance and tunneling spectroscopy of InAs quantum dots - Schmidt, K. H.; Bock, C.; Versen, M.; Kunze, U.; Reuter, Dirk; Wieck, A. D. (Journal of Applied Physics)

Hall magnetometry on Co, Fe, and Py nanowires - Reuter, Dirk; Hoch, S.; Hausmanns, B.; Stahlmecke, B.; Dumpich, G.; Wieser, R.; Nowak, U.; Wieck, A.D. (Journal of Magnetism and Magnetic Materials)

Radiatively limited dephasing in InAs quantum dots - Langbein, W.; Borri, P.; Woggon, U.; Stavarache, V.; Reuter, Dirk; Wieck, A. (Physical Review B)

Two relaxation mechanisms observed in transport between spin-split edge states at high imbalance - Deviatov, E. V.; Würtz, A.; Lorke, A.; Yu. Melnikov, M.; Dolgopolov, V. T.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Magnetotransport in C-doped AlGaAs heterostructures - Grbić, B.; Ellenberger, C.; Ihn, T.; Ensslin, K.; Reuter, Dirk; Wieck, A. D. (Applied Physics Letters)

Magnetic-field-induced excitons in photoluminescence from heavily doped p-type Ga1−xAlxAs/GaAs single heterojunction - Bryja, L.; Kubisa, M.; Ryczko, K.; Misiewicz, J.; Stȩpniewski, R.; Byszewski, M.; Potemski, M.; Reuter, Dirk; Wieck, A. (Physica B: Condensed Matter)

In-plane gate transistors in AlxGa1−xN/GaN heterostructures written by focused ion beams - Ebbers, A.; Reuter, Dirk; Heuken, M.; Wieck, A.D. (Superlattices and Microstructures)

Semiconductor Optics in Photonic Crystal Structures - Meier, Torsten; Koch, Stephan W. (Photonic Crystals: Advances in Design, Fabrication, and Characterization)

Temperature-controlled beam steering in polymer waveguide arrays - Pertsch, Thomas; Streppel, Ulrich; Zentgraf, Thomas; Dannberg, Peter; Braeuer, Andreas H.; Peschel, Ulf; Lederer, Falk L. (Linear, Nonlinear, and Power-Limiting Organics)

Hopping conductivity beyond the percolation regime probed by shot-noise measurements - Camino, F. E.; Kuznetsov, V. V.; Mendez, E. E.; Gershenson, M. E.; Reuter, Dirk; Schafmeister, P.; Wieck, A. D. (Physical Review B)

Fano resonances in semiconductor quantum dots - Fühner, C.; Keyser, U. F.; Haug, R. J.; Reuter, Dirk; Wieck, A. D. (physica status solidi (c))